A Self-Assembled and Flexible Supercapacitor based on Redox-Active Lignin-Based Nitrogen-Doped Activated Carbon Functionalized Graphene Hydrogels. Issue 5 (24th May 2021) - Cui, Linlin; Li, Yue; Jia, Mengying; Cheng, Chen; Jin, Xiaojuan
Abstract : Graphene material has a large theoretical specific surface area, excellent theoretical conductivity and mechanical flexibility, and is a promising electrode material for supercapacitors. However, two-dimensional graphene sheets are easy to stack, which affects its electrical properties. Specifically, a sponge-like composite hydrogel for high-performance supercapacitors was prepared by one-step hydrothermal method from activated carbon and graphene oxide. Benefiting from the introduced nitrogen-containing groups and the greatly increased specific surface area, the GAC-2 nitrogen-doped activated carbon/graphene hydrogel electrode showed high specific capacitance of 505.6 F g −1 . In addition, the composite hydrogel presented an excellent 3D network structure with abundant internal structural pores, in which graphene and activated carbon were cross-linked by strong covalent bonds. This unique structure greatly improves the mechanical flexibility of the composite electrode (the capacitance retention rate is approximately 87.7% after 500 bending tests). And the self-assembled flexible supercapacitor shows an energy density of 26.9 Wh kg −1 at 242 W kg −1 and outstanding capacitance retention rate of about 92.1% after 5000 charge-discharge cycles, confirming its potential application in supercapacitors.